Incidence and Predictors of Severe Adverse Drug Reactions among Patients on Antiretroviral Drugs in Harari Regional State, Eastern Ethiopia - Obsa Anbessa; Behailu Hawulte; Tariku Dingeta; Abdi Birhanu (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. The introduction of combination antiretroviral therapy improves the quality and longevity of people living with HIV/AIDS. However, adverse drug reactions associated with antiretroviral therapy compromise the resulting benefits and have been reported differently worldwide, including Ethiopia. Severe adverse drug reactions are one of the major public health concerns for the reason that they can potentially impede the benefit of antiretroviral therapy and put the patient’s survival at risk. Despite many successes achieved with the introduction of the combined antiretroviral therapy, the majority of the patients on antiretroviral therapy experience adverse drug reactions associated with the drugs. Consequently, little is known about the problem in the current study area. This is, therefore, to study incidence and predictors of severe adverse drug reactions among patients on antiretroviral drugs in the Harari region, Eastern Ethiopia. The aim of this study was to assess the incidence and predictors of severe adverse drug reactions among patients on antiretroviral therapy from February 25, 2022, to March 25, 2022, in the Harari region, Eastern Ethiopia. Methods. A hospital-based retrospective cohort study was conducted among 449 randomly selected medical records of people living with HIV on first-line antiretroviral therapy. Collected data were entered into EpiData version 3.1 and exported to STATA version 15 for analysis. Kaplan–Meier survival curve with log-rank test was used to compare survival curves for categorical independent variables. A p value ≤0.05 was declared as significant, and an adjusted hazard ratio was used to report the effect size using the multivariate Cox proportional hazard model. Result. The overall incidence density of the severe adverse reactions was 7.22 per 1000 months (95% CI: 5.5, 9.6). After adjusting for all potential confounders using multivariable Cox proportional hazard ratio, advanced clinical diseases (AHR = 3.44; 95% CI: 1.54, 7.65), HIV/tuberculosis confections (AHR = 2.38; 95% CI: 1.23, 4.62), and being female (AHR = 3.12; 95% CI: 1.57, 6.18) were significantly associated with the experience of severe adverse drug reactions. Conclusion. In this study, the incidence of severe adverse reactions was consistent with the previous studies, and advanced World Health Organization (WHO) clinical stage, HIV/TB confection, and being female were the independent predictors of the severe adverse drug reactions.